2009
DOI: 10.1007/s10532-008-9245-8
|View full text |Cite
|
Sign up to set email alerts
|

Biological sulphate reduction using food industry wastes as carbon sources

Abstract: Biological treatment with dissimilatory sulphate-reducing bacteria has been considered the most promising alternative for decontamination of sulphate rich effluents. These wastewaters are usually deficient in electron donors and require their external addition to achieve complete sulphate reduction. The aim of the present study was to investigate the possibility of using food industry wastes (a waste from the wine industry and cheese whey) as carbon sources for dissimilatory sulphate-reducing bacteria. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 40 publications
5
33
0
Order By: Relevance
“…1). Martins et al (2009) have reported similar pattern of sulphate reduction during the assessment of food industry wastes as carbon sources in biological sulphate reduction processes. In spite of efficient sulphate reduction performances in the first halves, all the isolates showed extended lag phases showing negligible growth in the initial 10 days of anaerobic incubation periods (Fig.…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…1). Martins et al (2009) have reported similar pattern of sulphate reduction during the assessment of food industry wastes as carbon sources in biological sulphate reduction processes. In spite of efficient sulphate reduction performances in the first halves, all the isolates showed extended lag phases showing negligible growth in the initial 10 days of anaerobic incubation periods (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…Prevalence and dominance of Desulfovibrio genus in sulphate rich and anaerobic environments is best studied (Dar et al 2005;Martins et al 2009). Following the BLAST results the bacteria were identified as Desulfovibrio fructosovorans and Desulfovibrio piger.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations